2017
DOI: 10.1155/2017/1821837
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Efficiency of Dye-Sensitized Solar Cells by Growing Longer ZnO Nanorods on TiO2 Photoanodes

Abstract: By increasing the temperature of hydrothermal reactions from 70 to 100 ∘ C, vertically aligned ZnO nanorods were grown on the TiO 2 thin film in the photoanode of dye-sensitized solar cells (DSSCs) as the blocking layer to reduce the electron back recombinations at the TiO 2 /electrolyte interfaces. The length effects of ZnO nanorods on the photovoltaic performances of TiO 2 based DSSCs were investigated by means of scanning electron microscope, X-ray diffractometer, photoluminescence spectrophotometer, and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Chander et al 213 recently demonstrated that YVO 4 :Eu 3+ nanophosphors on a TiO 2 photoanode enhanced the absorbance and environmental stability of dye-sensitized solar cells. The efficiency of dye-sensitized solar cells using ZnO nanorods with decorated TiO 2 thin film as the photoanode was reported to have increased by Zhai et al 214 These improvements can be attributable to the longer ZnO nanorods' higher surface area and lower flaw density. The circumstances are favorable for increased dye absorption and improved transport efficiency in the photoanode.…”
Section: Downshifting Materials For Photovoltaic Applicationsmentioning
confidence: 99%
“…Chander et al 213 recently demonstrated that YVO 4 :Eu 3+ nanophosphors on a TiO 2 photoanode enhanced the absorbance and environmental stability of dye-sensitized solar cells. The efficiency of dye-sensitized solar cells using ZnO nanorods with decorated TiO 2 thin film as the photoanode was reported to have increased by Zhai et al 214 These improvements can be attributable to the longer ZnO nanorods' higher surface area and lower flaw density. The circumstances are favorable for increased dye absorption and improved transport efficiency in the photoanode.…”
Section: Downshifting Materials For Photovoltaic Applicationsmentioning
confidence: 99%
“…This proves that the size of the diameter and absorbance at the photoanode which is influenced by a good seed solution will affect the performance of DSSCs. The smaller diameter of the ZnO nanorod in sample 2 provides a larger surface area then increasing the total amount of dye attached to the ZnO nanorod and improve the photovoltaic performance [20].…”
Section: The Photovoltaic Performance Of Dsscs Based Zno Nanorodsmentioning
confidence: 99%